Local Wisdom of Nusantara Architecture as Sustainable Architecture That Responds to Nature and The Environment (International Conference of Graduate School on Sustainability (ICGSS), 2021)
Indonesia is an area consisting of many islands so it was formerly called the Nusantara. The Nusantara is influenced by the confluence of some of the most seismically active tectonic plates in the world. The Nusantara is an earthquake-prone area because it is located in the ring of the fire area. The Nusantara is also a humid tropical region with relatively hot air temperatures and high rainfall. These natural and environmental conditions are a challenge for the people of the Nusantara to build their dwellings. In responding to these natural challenges, various "intelligent" architectural designs of the Nusantara of the past have been realized. With limited equipment and knowledge of building structures, as well as the use of local materials, an architectural work that is adaptive and harmonious and pays attention to environmental sustainability is realized. Long before the environmental sustainability aspect was echoed by the United Nations through the SDGs, it turned out that the people of the Nusantara had first practiced it directly in their lives. This article was written with an explanatory descriptive method, a literature study approach using secondary data from several previous research articles grouped into several categories and discussions. This paper aims to show a small part of the "intelligence" of architectural design in the ancient Nusantara, so that it can inspire sustainable and contemporary architectural works of the Nusantara (Indonesia).